Reward governance for senior executives / edited by Carol Arrowsmith and Rupert McNeil. - Arrowsmith, Carol, 1954-; McNeil, Rupert (Law practitioner series., 2008)
In areas such as dispute resolution, visibility and investor interest, the relationship between a senior executive employee and his or her employer differs materially from the relationship that most employees have with their employer. Executives are tools which help create shareholder value. A company's decision to employ one executive over another should be based on the ability of the potential employees to create shareholder value for the organisation. It is therefore essential to get both the appointment and contract right. Negotiating and agreeing the right contract requires an understanding of areas as diverse as valuation, employment law, tax and accounting. Covering the appointment of UK executives under contracts governed by UK law, this volume of essays is intended to help anyone involved in the appointment and termination process.